RETRACTED: Effect of Bimetal Element Doping on the Low-Temperature Activity of Manganese-Based Catalysts for NH3-SCR - Li, Haixia; Zhang, Shuaibo; Zhang, Anchao; Zhang, Xinmin; Sun, Zhijun; Yang, Changze; Zhu, Qifeng (Frontiers in Chemistry, 2022)
A series of novel Mn6Zr1-xCox denitrification catalysts were prepared by coprecipitation method. The effect of co-modification of MnOx catalyst by zirconium and cobalt on the performance of NH3-SCR was studied by doping transition metal cobalt into Mn6Zr1 catalyst. The ternary oxide catalyst Mn6Zr0.3Co0.7 can reach about 90% NOx conversion in a reaction temperature range of 100-275℃, and the best NOx conversion can reach 99%. In addition, the sulfur resistance and water resistance of Mn6Zr0.3Co0.7 catalyst were also tested. When the concentration of SO2 is 200ppm, the NOx conversion of catalyst Mn6Zr0.3Co0.7 is still above 90%. 5Vol% H2O has little effect on catalyst NOx conversion. The results show that Mn6Zr0.3Co0.7 catalyst has excellent resistance to sulfur and water. Meanwhile, the catalyst was systematically characterized. The results show that the addition of zirconium and cobalt changes the surface morphology of the catalyst. The specific surface area, pore size and volume of the catalyst were increased, and the reduction temperature of the catalyst was decreased. In conclusion, the doping of zirconium and cobalt successfully improves the NH3-SCR activity of the catalyst.